Rules to be applied for the organisation of road cycling competitions in the context of the COVID-19 pandemic - Barrio, J.; Bigard, X.; Boelens, A.; Cerfontaine, M.; Chassot, R.; Clignet, M.; Jan, X.; Lopes, A.; Nash, K.; Sprouse, K.; Thouault, P.-Y. (UCI, 2021)
The stakeholders of cycling and the UCI acknowledge the extraordinary nature of the COVID-19 prevailing since 2020 and the ensuing difficulties for the organisation of safe sporting events. These are all the more acute in the context of cycling events due to the regular international travel, the use of free-access venues and facilities and the different team and staff compositions From the beginning of the pandemic, the UCI and stakeholders of cycling agreed to constitute the UCI Steering Group to present to the UCI Management Committee a set of emergency rules (hereinafter: the Rules) with the objective of reducing the risk of transmission of the coronavirus during events of the UCI International Calendar. Since the end of the 2020 road cycling season new events have occurred that must be taken into consideration for the organisation of road events on the UCI international calendar. Indeed, - the development, validation by many health authorities, and dissemination of several vaccines against COVID-19, - the new advances in the design of antigenic tests, - the appearance of mutations in the viral genome, causing changes in the host-pathogen interactions. impose to update the Rules for the organization of road races that had been applied for the 2020 season. As for the 2020 season, the present document should not be a "consensus statement" per se. Upon agreement within the UCI Steering Group, these Rules were presented to and approved by the UCI Management Committee in accordance with article 47.1 lit. k) of the UCI Constitution. The Rules include requirements, instructions (mandatory measures) and present recommendations for good practice (recommended and desired measures) for organising cycling events during the COVID-19 pandemic.